Incorporation of Genetic Studies in the Kidney Transplant Evaluation Clinic: The Value of a Multidisciplinary Approach. Issue 4 (31st March 2023) - El Ters, Mireille; Pinto e Vairo, Filippo; Prochnow, Carri; Schinstock, Carrie; Dean, Patrick; Kemppainen, Jennifer; Lazaridis, Konstantinos; Cosio, Fernando; Fervenza, Fernando C.; Cornell, Lynn; Amer, Hatem; Hogan, Marie C.
Abstract : Background: Recent studies identified underlying genetic causes in a proportion of patients with various forms of kidney disease. In particular, genetic testing reclassified some focal segmental glomerulosclerosis (FSGS) cases into collagen type 4 (COL4)-related nephropathy. This knowledge has major implications for counseling prospective transplant recipients about recurrence risk and screening biologically related donors. We describe our experience incorporating genetic testing in our kidney transplant multidisciplinary practice. Methods: Patients' DNA was analyzed using whole exome sequencing for a comprehensive kidney gene panel encompassing 344 genes associated with kidney diseases and candidate genes highly expressed in the kidney. Results were correlated with phenotype by a multidisciplinary committee of nephrologists, renal pathologists, geneticists, and genetic counselors. Between October 2018 and July 2020, 30 recipient and 5 donor candidates completed testing. Results: Among recipient candidates, 24 (80%) carried the diagnosis of FSGS, 2 (6.7%) tubulointerstitial nephritis, and 1 (3.3%) nephrolithiasis, and 3 (10%) had an unknown cause of kidney disease. The yield for pathogenic/likely pathogenic variants was 43.3%, with majority being COL4 variants (53.8%). Among those with FSGS diagnosis, the yield was 10 of 24 (41.6%), with 29% reclassified into a COL4-related nephropathy. Family history of kidney disease was the only clinical characteristic difference between recipients with positive and negative results (76.9 versus 29.4%; P = 0.025). One of 5 donors tested positive for a pathogenic/likely pathogenic variant and was excluded from donation. Conclusions: We conclude that thoughtful use of genetic testing can be valuable for kidney donor selection and transplant recipient management.